The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.33788/rcis.64.6
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of Service Recovery on Customer Loyalty Based On Marketing Word Of Mouth in Tourism Industry

Abstract: Akamavi, R K., Mohamed, E., Pellmann, K., & Xu, Y. (2015). Key determinants of passenger loyalty in the low-cost airline business. Tourism Management, 46, 528-545. Baldus, B.J., Voorhees, C., & Calantone, R. (2015). Online brand community engagement: Scale development and validation. Journal of Business Research, 68(5), 978-985. Boo, H.V. (2017). Service Environment of Restaurants: Findings from the youth customers. Journal of Asian Behavioural Studies, 2(2), 67-77. Bowen, T.J., & Chen, S.L. (2015)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…After a service failure, customers often expect the service provider to consider steps to ensure service recovery (Pai et al, 2019). Keiningham et al (2014) found that the severity of service failure significantly impacted recovery expectations in industrial companies.…”
Section: Relationship Between Service Recovery and Customer Loyaltymentioning
confidence: 99%
See 2 more Smart Citations
“…After a service failure, customers often expect the service provider to consider steps to ensure service recovery (Pai et al, 2019). Keiningham et al (2014) found that the severity of service failure significantly impacted recovery expectations in industrial companies.…”
Section: Relationship Between Service Recovery and Customer Loyaltymentioning
confidence: 99%
“…Service recovery is the action of the service provider to resolve customer service failure complaints (Dong et al, 2008). Service recovery aims to turn customer dissatisfaction into a satisfied condition that can build company relationships with customers (Pai, Ko and Santos, 2019). From the literature above, the proposed hypothesis is as follows:…”
Section: Relationship Between Service Recovery and Customer Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…eEWOM is especially important for intangible products, which are difficult to evaluate for consumer choices; for example, in tourism or hotels, the overall satisfaction of the consumers will affect the behavioral decisions of others [23]. This circumstance has made eWOM becomes a more reliable medium [24].…”
Section: B Ewom Researchmentioning
confidence: 99%
“…The current literature discusses the quality measurement system of online shopping service recovery (Liu and Li, 2017) and the relationship between online shopping service, service recovery, and customer satisfaction and loyalty (Jian and Ke, 2017). At present, academic circles have also studied the impact of word-of-mouth on the service recovery effect of travel agencies, and the service recovery effect is measured by customer satisfaction and customer loyalty (Pai et al, 2019). They developed a practical manual on service failure and service recovery for the travel industry (Inkson, 2019).…”
Section: Introductionmentioning
confidence: 99%